Scouting for Insects, Use of Thresholds and Conservation of Beneficial Insects on Tomatoes - David J. Schuster (EDIS)
This article provides a description of the rationale of scouting methodology, action thresholds, and pesticide selection criteria for tomatoes. This document is ENY685, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date June 2003.